FIRE RISK MANAGEMENT AT PT PERTAMINA EP ASSET 4 FIELD SUKOWATI - Maulana Yakub; Sisca Mayang Phuspa (Journal of Industrial Hygiene and Occupational Health, 2019)
Fire is a common risk in the oil and gas processing industry such as PT Pertamina Asset 4 Field Sukowati. Fire risk management is important to prevent large damages and losses in the  fire incidence. This study aims to describe fire risk management at PT Pertamina Asset 4 Field Sukowati. It is hoped that it can be useful as a reference for evaluating companies to improve fire risk management performance. This research is classified as observational descriptive research with purposive sampling data collection method. The analysis of the study used the Risk Management based on AS / NZS 4360: 2004 reference. The results showed that fire risk at PT Pertamina Asset 4 in Sukowati Field based on the stages of work varied from low, medium to high. The fire protection system at PT Pertamina Aset 4 Field Sukowati generally shows good conditions and is well monitored. Fire emergency response planning and organization are also adequate. Unfortunately, fire emergency response simulations have not been carried out regularly, so evaluating the success of fire risk management programs is difficult to measure. The recommendation in this study is the measurement of workers' preparedness as a follow-up to the implementation of fire emergency response simulations. It is because high worker preparedness is the key to implementing good fire risk management.Keyword: Risk management; Fire; PT Pertamina